2017
DOI: 10.1108/apjml-07-2016-0128
|View full text |Cite
|
Sign up to set email alerts
|

Importance of acquiring knowledge through feedback in an emerging industry

Abstract: Purpose The purpose of this paper is to investigate the importance of feedback in developing and operationalising knowledge from the perspective of craft brewing operators. The study contributes to various literature streams, including marketing and craft brewing entrepreneurship. An additional contribution is made through the adoption of the knowledge-based theory of the firm, and the SECI process to facilitate understanding of the significance of knowledge in the craft brewing industry. Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Social capital has been a crucial component in understanding entrepreneurial performance (Stam et al, 2014). Numerous studies have demonstrated the benefits of social capital for new ventures including greater access to information (Birley, 1985), emotional support (Brüderl and Preisendörfer, 1998), competitive capabilities (McEvily and Zaheer, 1999), financial capital (Batjargal, 2003), legitimacy development (Elfring and Hulsink, 2003), opportunity identification (Bhagavatula et al, 2010) and entrepreneurial performance (Stam and Elfering, 2008; Stam et al, 2014).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…Social capital has been a crucial component in understanding entrepreneurial performance (Stam et al, 2014). Numerous studies have demonstrated the benefits of social capital for new ventures including greater access to information (Birley, 1985), emotional support (Brüderl and Preisendörfer, 1998), competitive capabilities (McEvily and Zaheer, 1999), financial capital (Batjargal, 2003), legitimacy development (Elfring and Hulsink, 2003), opportunity identification (Bhagavatula et al, 2010) and entrepreneurial performance (Stam and Elfering, 2008; Stam et al, 2014).…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The framing of CBT as fixated on brewers/breweries, and tourists may elucidate insights for a better understanding of the host–guest relations, yet they are not the only part of the wider value chain that engages in this niche market. Few studies were found to delve into other stakeholder inputs from the perspectives of agritourism, hotels and accommodation providers, tour operators, suppliers and residents, for instance, as postulated by other scholars (Alonso and Alexander, 2017a; Backman et al , 2021b). Furthermore, recent studies have probed the experiential and social capital manifestations of craft beer developments and are using more immersive methods such as ethnography, visual artefacts (e.g.…”
Section: Overview Of Methodsmentioning
confidence: 99%
“…The classic work of Nonaka and Takeuchi's SECI Model (1995) is still pertinent in understanding knowledge general processes in organizations. The SECI Model (Nonaka & Takeuchi, 1995) has been getting attention in numerous disciplines such as management engineering (Feng & Yu, 2018), commerce (Chaanouni & Yahira, 2014), education (Brundrett & Lungka, 2018), management (Chatterjee et al, 2018), and marketing (Alonso & Alexander, 2017). Nonaka and Takeuchi (1995) developed a knowledge creation model based on their findings between Western and Japanese culture on knowledge creation.…”
Section: A Knowledge Creation Within An Organizationmentioning
confidence: 99%